The Relationship between Equity-based Compensation and Firm Performance: Evidence from Chinese Listed Companies - Zhang, Ying (2020)
The purpose of this dissertation is to investigate the role of equity-based compensation on firm performance, using a sample of 1572 firm-year observations from the listed companies in China's Shanghai and Shenzhen Stock Exchange. And the sample period is from 2014 to 2018. Firm performance is measured by two accounting-based measures, return on asset (ROA), return on equity (ROE), and a market-based measure, Tobin’s Q. The equity-based compensation is divided into equity-based compensation for executives and that for employees. The static panel data analysis is used for estimation. After controlling the effects of the unobserved firm-specific features, the study finds that equity incentives for executives are negatively related to firm performance, while equity incentives for employees can improve firm performance. However, the number of shares currently used for equity incentives is small as a percentage of total capital, resulting in that the effect of equity incentive plans on company performance is quite limited. The results also show that the leverage, firm size, growth rate of net profit, total asset turnover, and ownership of concentration have significant impacts on at least one of the proxies of firm performance.